711PThe analysis of genomic signatures of head and body/tail of pancreatic cancer in Chinese patients. (1st October 2019) - Ling, Q; Huang, H; Zhang, X; Rui, T; Feng, S; Wang, Q; Huang, Y; Zhang, S; Wang, A; Yao, M; Wang, K
Abstract: Background: The incidence of pancreatic cancer (PAC) has continued to rise in recent years. PAC can be divided into head of PAC (HPAC) and body/tail of PAC (BTPAC) by the anatomical location. The patients (pts) with BTPAC are usually diagnosed at relatively advanced stage and had worse survival than those with HPAC. The comparative molecular signatures between different locations in Chinese PAC pts remain unclear. Methods: 154 tumor specimens (HPAC, N = 85; BTPAC, N = 69) and matched normal blood samples of Chinese PAC pts were detected and analyzed in a CAP&CLIA certified laboratory (OrigiMed company) with Yuansu panel including 450 genes. Total 100 males (65%) and 54 females (35%) with a mean age of 61 years old (yrs) were enrolled. We measured the somatic variations and calculated tumor mutational burden (TMB) after filtering known driver mutations (muts). Meanwhile, germline muts were analyzed among the tumor susceptibility genes. Fisher tests were used for comparative analyses. Results: The median age in HPAC and BTPAC was 60 yrs and 62 yrs. Pts with stage 3&4 accounted for 40% and 60% in HPAC and BTPAC ( P <0.05). Genomic alterations of KRAS and SMAD4 were significantly more prevalent in BTPAC (KRAS in BTPAC vs. HPAC= 97% vs. 82%, P =0.004; SMAD4 in BTPAC vs. HPAC= 42% vs. 21%, P =0.008). 2 NTRK3 fusions (3%) were found in BTPAC but 0 in HPAC. Additionally, muts frequency in Wnt pathway was 57% in BTPAC, whereas 37% in HPAC ( P =0.02). No significant difference was found in TP53 (83% vs. 81%), CDKN2A (32% vs. 27%) and germline muts frequency (12% vs. 14%) between BTPAC and HPAC, nor in the mean TMB value (3.22 muts/Mb vs. 3.59 muts/Mb). For HPAC, there were more muts in HR pathway genes (24% vs. 19%), although the difference was not statistical significance. 2 BRCA2 germline muts were found in HPAC but neither BRCA1 nor BRCA2 was found in BTPAC. Conclusions: Genomic pattern did not show apparent difference between the anatomic locations of PAC. However, we found more driver muts in KRAS and SMAD4 and more Wnt pathway muts related to proliferation and metastasis in BTPAC. Further research should be done to better understand the cancer biology among the locations and identify more therapy targets for precision medicine. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.